KUALITAS FISIKA, KIMIA, DAN MIKROBIOLOGI AIR TAP UNIVERSITAS SEBELAS MARET SURAKARTA - Yovanisa Meirawati; Tjahjadi Purwoko; Ratna Setyaningsih (Biospektrum Jurnal Biologi, 2023)
Universias Sebelas Maret (UNS) Surakarta has a piped drinking water distribution system. Drinking water from a piped system is called tap water. Tap water is a public facility provided by the government in European cities but not in Indonesia. However, consumption of tap water by the academic community at UNS Surakarta was relatively low. This was caused by the trust and worthiness of UNS’s tap water. This research aimed to determine the quality of tap water at UNS Surakarta, both in aspects of physics, chemistry and microbiology. Selection of sampling points based on the location of the distribution pipes and sampling using the grab sampling method. The tap water analyzed by Indonesian National Standard (SNI) test for drinking water. The results were compared with the Indonesian Government Regulation on Drinking Water, namely PERMENKES 492/2010. The quality of physical, chemical and microbiological aspects of tap water at UNS Surakarta were meet Indonesian Government Regulations, namely Permenkes 492/2010. Thus, tap water from UNS Surakarta is equivalent to bottled drinking water and worth to drink.